(untitled) (Global Journal of Medical Research, 2020)
Milk ethanol stability is defined as the minimum concentration of added aqueous ethanol giving rise to milk coagulation. The milk, which shows a positive reaction to the alcohol test, is usually graded as second rate and diverted for butter making but not condensed milk. The ions calcium, potassium, and chlorides are mainly responsible for the alcohol instability of milk. As there is no rational method to convert ethanol sensitive-milk to ethanol-insensitive one, we attempted to test and remove this bad quality with two homeopathic remedies, KaliMuririaticum 200 and Calcarea Phosphorica 12 x. We gave these medicines for seven days to16 cows whose milk was sensitive to 70% alcohol. The results were dramatic and proved the high efficacy of the homeopathic system of medicine, and gave conclusive evidence that ions calcium and chlorides are responsible for milk instability. Kali mur 200(higher potency) removed the detrimental effects of potassium and chlorides and calcarean phos12 x (lower potency) fortified the alcohol stability of milk. Both the remedies acted synergistically.